Safety in Rib Surgery: A Meta-analysis and Systematic Review - Raúl Martín Manzaneda Cipriani, MD; Héctor Durán Vega, MD; José J. Bucio Duarte, MD; Daniel Botelho, MD; Yuri Jiménez Caprielova, MD; José M. Zepeda Torres, MD; Raul Gonzalez, MD; Luis R. Jiménez Hernández (Plastic and Reconstructive Surgery, Global Open)
Background:. Cosmetic rib reshaping has gained popularity in recent years as a technique for enhancing body contour, particularly around the waist. However, the safety of these interventions remains a topic of debate due to the proximity of the ribs to vital organs such as the lungs and heart. This meta-analysis aimed to evaluate the safety profile of rib reshaping techniques based on existing studies. Methods:. We conducted a systematic review and meta-analysis of all available studies on rib surgery for cosmetic purposes. The literature search included databases such as PubMed, Scopus, Embase, Cochrane, and Google Scholar. A total of 7 studies involving 395 patients were included. We analyzed intraoperative and postoperative complications, as well as patient satisfaction levels. Results:. The analysis revealed that rib reshaping techniques have an acceptable safety profile, with a low incidence of complications. Reported complications included pneumothorax (1.9%), skin burns (6.7%), residual contour asymmetry (2.3%), and severe postoperative pain (9.2%). Despite these complications, patient satisfaction levels were high, indicating a favorable balance between aesthetic risks and benefits. Conclusions:. Rib surgery for cosmetic purposes, although not without risk, is demonstrated to be a safe procedure when performed by experienced surgeons and in appropriately selected patients. The techniques reviewed in this meta-analysis show a low incidence of serious complications and high levels of patient satisfaction, suggesting that with proper postoperative management, significant aesthetic results can be achieved with minimal risk. Standardized outcome measures and larger clinical trials are needed to improve safety and consistency in results.